2021
DOI: 10.1007/s12015-021-10175-1
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Potential of Genetically Modified Stem Cells in the Treatment of Stroke: a Review

Abstract: The last two decades have witnessed a surge in investigations proposing stem cells as a promising strategy to treat stroke. Since growth factor release is considered as one of the most important aspects of cell-based therapy, stem cells over-expressing growth factors are hypothesized to yield higher levels of therapeutic efficiency. In pre-clinical studies of the last 15 years that were investigating the efficiency of stem cell therapy for stroke, a variety of stem cell types were genetically modified to over-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…Since all of these processes are essential for recovery after stroke, numerous investigations employed exogenous growth factors to treat cerebral ischemia [ 45 ]. In addition, the beneficial potential of genetically engineered stem cells over-expressing growth factors has been demonstrated in the treatment of stroke [ 46 ]. It is documented that BDNF expression increased following different types of stroke such as intracerebral hemorrhage [ 47 ] and ischemic stroke [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since all of these processes are essential for recovery after stroke, numerous investigations employed exogenous growth factors to treat cerebral ischemia [ 45 ]. In addition, the beneficial potential of genetically engineered stem cells over-expressing growth factors has been demonstrated in the treatment of stroke [ 46 ]. It is documented that BDNF expression increased following different types of stroke such as intracerebral hemorrhage [ 47 ] and ischemic stroke [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that overexpression of glial cell line‐derived neurotrophic factor (GDNF) regulates the expression of a diversity of genes like neuregulin1, ephrinB2‐receptor, neuritis, and focal adhesion kinase (FAK) in NSCs, thus directly influencing differentiation and developmental processes of neurons 105 . Likewise, although direct administration of brain‐derived neurotrophic factor (BDNF) provides no long‐term effects as a result of the short half‐life of BDNF, 106 its overexpression could increase the engrafted NSCs viability, neuronal fate, neurite complexity, maturation of electrical property as well as the synaptic density in vivo 107 . BDNF binds to its high‐affinity receptor tyrosine kinase B (TrkB) and subsequently induces the activation of signaling cascades, such as the Ras‐mitogen‐activated protein kinase (MAPK), the phosphatidylinositol‐3‐kinase (PI3K), and the phospholipase Cγ (PLC‐γ) signaling pathways 108,109 .…”
Section: The Importance Of Engineering Of Nscsmentioning
confidence: 99%
“…Although endogenous neural stem cells (NSCs) do exhibit an acute response to IS, such as increased cell proliferation and cell migration, only 10%-20% of these cells survive long-term, and only a few of these surviving cells can mature into functional cells. However, most of them develop into thorny new striatal projection neurons or calretinin-positive interneurons 84 . This hinders the differentiation of MSCs into functional nerve cells after transplantation.…”
Section: Application Of Modified Mscs In the Treatment Of Ischemic St...mentioning
confidence: 99%